Long-term effects of the Family Bereavement Program on spousally bereaved parents: Grief, mental health problems, alcohol problems, and coping efficacy. (18th July 2016) - Sandler, Irwin; Tein, Jenn-Yun; Cham, Heining; Wolchik, Sharlene; Ayers, Tim
Abstract: This study reports on the findings from a 6-year follow-up of a randomized trial of the Family Bereavement Program (FBP) on the outcomes for spousally bereaved parents. Spousally bereaved parents ( N = 131) participated in the trial in which they were randomly assigned to receive the FBP ( N = 72) or literature control ( N = 59). Parents were assessed at four time points: pretest, posttest, and 11-month and 6-year follow-up. They reported on mental health problems, grief, and parenting at all four time periods. At the 6-year follow-up, parents reported on additional measures of persistent complex bereavement disorder, alcohol abuse problems, and coping efficacy. Bereaved parents in the FBP as compared to those in the literature control had lower levels of symptoms of depression, general psychiatric distress, prolonged grief, and alcohol problems, and higher coping efficacy (for mothers) at the 6-year follow-up. Multiple characteristics of the parent (e.g., gender, age, and baseline mental health problems) and of the spousal death (e.g., cause of death) were tested as moderators of program effects on each outcome, but only 3 of 45 tests of moderation were significant. Latent growth modeling found that the effects of the FBP on depression, psychiatric distress, and grief occurred immediately following program participation and were maintained over 6 years. Mediation analysis found that improvement in positive parenting partially mediated program effects to reduce depression and psychiatric distress, but had an indirect effect to higher levels of grief at the 6-year follow-up. Mediation analysis also found that improved parenting at the 6-year follow-up was partially mediated by program effects to reduce depression and that program effects to increase coping efficacy at the 6-year follow-up was partially mediated through reduced depression and grief and improved parenting. FBP reduced mental health problems, prolonged grief, and alcohol abuse, and increased coping efficacy of spousally bereaved parents 6 years later. Mediation pathways for program effects differed across outcomes at the 6-year follow-up.